Neonatal androgenization exacerbates alcohol-induced liver injury in adult rats, an effect abrogated by estrogen. - Whitney M Ellefson; Ashley M Lakner; Alicia Hamilton; Iain H McKillop; Herbert L Bonkovsky; Nury M Steuerwald; Yvette M Huet; Laura W Schrum (PLoS ONE)
Alcoholic liver disease (ALD) affects millions of people worldwide and is a major cause of morbidity and mortality. However, fewer than 10% of heavy drinkers progress to later stages of injury, suggesting other factors in ALD development, including environmental exposures and genetics. Females display greater susceptibility to the early damaging effects of ethanol. Estrogen (E2) and ethanol metabolizing enzymes (cytochrome P450, CYP450) are implicated in sex differences of ALD. Sex steroid hormones are developmentally regulated by the hypothalamic-pituitary-gonadal (HPG) axis, which controls sex-specific cycling of gonadal steroid production and expression of hepatic enzymes. The aim of this study was to determine if early postnatal inhibition of adult cyclic E2 alters ethanol metabolizing enzyme expression contributing to the development of ALD in adulthood. An androgenized rat model was used to inhibit cyclic E2 production. Control females (Ctrl), androgenized females (Andro) and Andro females with E2 implants were administered either an ethanol or isocalorically-matched control Lieber-DeCarli diet for four weeks and liver injury and CYP450 expression assessed. Androgenization exacerbated the deleterious effects of ethanol demonstrated by increased steatosis, lipid peroxidation, profibrotic gene expression and decreased antioxidant defenses compared to Ctrl. Additionally, CYP2E1 expression was down-regulated in Andro animals on both diets. No change was observed in CYP1A2 protein expression. Further, continuous exogenous administration of E2 to Andro in adulthood attenuated these effects, suggesting that E2 has protective effects in the androgenized animal. Therefore, early postnatal inhibition of cyclic E2 modulates development and progression of ALD in adulthood.